The control of state regional aids by the European competition policy and its effects on economic and social cohesion - Carmen Benavides; Margarita Arguelles Velez (European Regional Science Association (ERSA), 1998)
The economic activity of the countries which make up the European Union (EU) is being profoundly affected by the advance in the process of integration. The consolidation of the Single European Market (SEM) and the process of transition towards Economic and Monetary Union (EMU) are two elements which affect the economic evolution of all of teh countries and regions of the EU. The impact of this greater economic integration is expected to be reflected with different intensity in each of them, according to their own economic structures and their capacity of adaptation to the necessary convergence. The effect of this process on the development of the regions, in itself already unequal, has caused growing concern about the reinforcement of economic and social cohesion within the EU, as was reflected in the Treaty of the European Union. In this way, the steps taken towards a growing integration are complemented by a greater development of structural policies. The reinforcement of these policies, and in particular of regional policy, confers special importance to the analysis of its instruments, above all, to that of the programs for regional economic incentives. Economic incentive programs constitute one of the most widely used tools of regional policy among the member nations of the EU. Given the fact that this assistance is aimed at companies, it is subject to meet Community regulations on competition and, at the same time, as a measure for regional development, play a role in the attainment of economic and social cohesion. In this paper the most important aspects of this last component will be analyzed in terms of regional assistance in order to then proceed to the study of its effects on the correction of interregional inequality.
Keywords: 330